2004
DOI: 10.1002/lt.20108
|View full text |Cite
|
Sign up to set email alerts
|

The role of selective digestive decontamination for reducing infection in patients undergoing liver transplantation: A systematic review and meta-analysis

Abstract: Selective digestive decontamination (SDD) refers to the use of antimicrobials to reduce the burden of aerobic gram-negative bacteria and/or yeast in the intestinal tract to prevent infections caused by these organisms. Liver transplant patients are highly vulnerable to bacterial infection particularly with gram-negative organisms within the first month after transplantation, and SDD has been proposed as a potential measure to prevent these infections. However, the benefit of this procedure remains controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 50 publications
(96 reference statements)
1
38
0
8
Order By: Relevance
“…Although FQ-SID appeared to reduce the incidence of infections due to enteric bacteria in LTRs, this effect was not evident after adjustments by other variables, including the transplant center. A meta-analysis by Safdar et al 18 evaluating different SID modalities in LTRs showed a protective effect of SID against infections by enteric bacteria, but this did not translate into an overall reduction of the rate of EBIs because patients receiving SID had an increased incidence of enterococcal infections. We did not observe differences in the relative incidence of enterococcal infections with respect to the use of FQ-SID, but we did find a higher relative incidence of infections by NFGNBs in patients undergoing FQ-SID, which probably overrode the protective effect against infections due to enteric bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although FQ-SID appeared to reduce the incidence of infections due to enteric bacteria in LTRs, this effect was not evident after adjustments by other variables, including the transplant center. A meta-analysis by Safdar et al 18 evaluating different SID modalities in LTRs showed a protective effect of SID against infections by enteric bacteria, but this did not translate into an overall reduction of the rate of EBIs because patients receiving SID had an increased incidence of enterococcal infections. We did not observe differences in the relative incidence of enterococcal infections with respect to the use of FQ-SID, but we did find a higher relative incidence of infections by NFGNBs in patients undergoing FQ-SID, which probably overrode the protective effect against infections due to enteric bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…, Sadfar et al (10) and Silvestri et al (16) showed an impact on mortality. However, due to small sample size, the differences were not significant.…”
Section: Luciano Silvestrimentioning
confidence: 95%
“…Komplex antimikrobiális kezelés, amely az emésztőrendszerben található Gram-negatív baktériumok elleni prevenciót jelenti [11].…”
Section: Szelektív Digestiv Dekontamináció (Sdd)unclassified